Atherosclerotic renal artery stenosis, mediating biomarkers, and risk of cardiac among individuals with hypertension: A real-world study - Yanwei Li; Zhulu Chen; Rui Lan; Tao Ran; Jingyi He; Jialian Li; Qiuyue Shi; Min Mao; Zhong Zuo (International Journal of Cardiology: Heart & Vasculature)
Background: Atherosclerotic renal artery stenosis (ARAS) is commonly associated with cardiovascular diseases(CVD). Patients with ARAS typically present with cardiac structural and functional abnormalities, and the differences in cardiac structure and function compared to hypertensive patients without ARAS remain to be explored. Methods: A total of 499 hypertensive patients were included, of whom 134 had ARAS and 365 had no renal artery stenosis (RAS). Parameters about cardiac function and structure detected by echocardiography and other clinical data are collected. Univariate and multivariate binary logistic regression and mediation analysis were performed on the collected data. Results: Compared to hypertensive patients without ARAS, those with ARAS had significantly increased left ventricular (LV) internal diameter (LVIDd), posterior wall thickness (PWTd), LV geometric abnormalities, diastolic dysfunction, and a higher prevalence of LV hypertrophy (LVH). After adjustment, ARAS was significantly associated with LV diastolic dysfunction (LVDF) (OR = 1.12, 95 %CI = 1.03–1.3), LVIDd (OR = 1.07, 95 %CI = 1.02–1.13), LV geometry (OR = 1.24, 95 %CI = 1.12–1.36), PWTd (OR = 1.2, 95 %CI = 1.09–1.31), and LV mass index (OR = 1.31, 95 %CI = 1.18–1.47). Mediation analysis identified hypersensitive C-reactive protein (Hs-CRP) and serum creatinine (Scr) as significant mediators, accounting for 10.80 % to 59.54 % of the ARAS impact on LV abnormalities. Conclusion: ARAS appears to be an independent risk factor for abnormalities in cardiac function and structure, potentially mediated by Hs-CRP and Scr. Hypertensive patients with ARAS demonstrate a higher prevalence of left ventricular hypertrophy (LVH) and diastolic dysfunction, underscoring the importance of vigilant monitoring in this population.